Perlindungan Hukum Terhadap Konsumen Yang Dirugikan Dalam Mengkonsumsi Vitamin Penggemuk Badan Tanpa Label Bbpom Dalam Perspektif Hukum Positif Di Indonesia - Nadya, Baiq Shalsabilla; Hirsanuddin (Commerce Law, 2024)
The purpose of this study is to find out the legal protection that can be provided by consumers if they are harmed by the use of body-fattening vitamins based on Positive Law in Indonesia and to find out the legal responsibilities of business actors towards consumers who are harmed by the use of body fattening vitamins. This research is normative legal research that uses statute, conceptual, and approaches. The result of the study can be concluded; (1) Legal protection for consumers is contained in Article 19 Paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection, which regulates the legal responsibilities of business actors in sales and purchase agreements with consumers. (2) the responsibility of Businessmen who do not display the BBPOM label will be subject to administrative sanctions, imprisonment, or a fine.